Study on Gas-Phase Mechanism of Chloroacetic Acid Synthesis by Catalysis and Chlorination of Acetic Acid - Xue*, Jian-Wei; Zhang, Jian-Peng; Wu, Bo; Li, Fu-Xiang; Lv, Zhi-Ping (Asian Journal of Chemistry, 2014)
The process of acetic acid catalysis and chlorination for synthesizing chloroacetic acid can exist in not only gas phase but also liquid phase. In this paper, the gas-phase reaction mechanism of the synthesis of chloroacetic acid was studied. Due to the high concentration of acetic acid and the better reaction mass transfer in the liquid-phase reaction, the generation amount of the dichloroacetic acid was higher than that in the gas-phase reaction. Under the solution distillation, the concentration of acetyl chloride, whose boiling point is very low, was very high in the gas phase, sometimes even up to 99 %, which would cause the acetyl chloride to escape rapidly with the hydrogen chloride exhaust, so that the reaction slowed down. Therefore, series reactions occured easily in the gas-phase reaction causing the amount of the dichloroacetic acid to increase.